Antireflective ultra-fast nanoscale texturing for efficient multi-crystalline silicon solar cells. (May 2015) - Srivastava, Sanjay K.; Singh, Prashant; Yameen, Mohammad; Prathap, P.; Rauthan, C.M.S.; Vandana,; Singh, P.K.
Graphical abstract: (a) Reflectance of nT-mc-Si samples (S30, S60, S120 ) prepared for different etch time and that of chemically polished (control) silicon (SCP ) measured using integrating sphere, (b) solar weighted reflectance (SWR) of the nT-mc-Si samples with texturing/etch time (c) optical images of nT-mc-Si samples. Highlights: A simple and fast nanoscale texturing process for multi-crystalline Si is reported. Low solar weighted reflectance (<3%) in broad range is achieved in 30 s of texturing. Proof of concept of nanoscale-textured mc-silicon solar cell is presented. An improvement of ∼20% in photo current and ∼1.8% in efficiency is achieved. Results are supported by quantum efficiency, LBIC and carrier lifetime measurements. Abstract: Minimization of reflection losses is extremely important for efficient silicon solar cells made either on mono crystalline (c-) or multi-crystalline (mc-) silicon (Si) substrates. A simple and fast etching process yet effective for nano-scale texturing of mc-Si surface using silver assisted wet chemical etching is reported. This results in very low reflecting (<3%) mc-Si surface in the broad (300–1100 nm) spectral range in a short duration (∼30 s) of etch time. The process is applied successfully to produce black mc-Si solar cell with n + –p–p + structure wherein n + emitter and p + back surface field are made by phosphorus and aluminum diffusion respectively. A significant increase (∼20%) in the short circuit current is observed in the nano-textured mc-Si solar cell as compared to the control cell (processed in the same batch) without any deleterious effect on other performance parameters. The improved performance of the nano-textured cell is also confirmed by light beam induced current measurements. It is a "proof of concept" of a simple, fast and inexpensive etching process to realize anti-reflective surface on mc-Si with improved solar cell performance and have potential for industrial solar cell application.